2016
DOI: 10.1186/s12913-016-1392-8
|View full text |Cite
|
Sign up to set email alerts
|

Medical doctors in healthcare leadership: theoretical and practical challenges

Abstract: BackgroundWhile healthcare systems vary in their structure and available resources, it is widely recognized that medical doctors play a key role in their adaptation and performance. In this article, we examine recent government and organizational policies in two different health systems that aim to develop clinical leadership among the medical profession. Clinical leadership refers to the engagement and guiding role of physicians in health system improvement. Three dimensions are defined to conduct our analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 43 publications
3
76
0
Order By: Relevance
“…New modes of governing focused on physicians not only as objects but also as actors directly involved in governance (Kuhlmann et al 2013, McDonald et al 2008, Vicarelli and Pavolini 2017. As a result, boundaries between professionalism and managerialism and between professions and organisations are 'blurring' and new forms of more hybrid, integrated or transformative professionalism are emerging (Denis and van Gestel 2016, Kuhlmann and Burau 2015, Martin et al 2017, Noordegraaf 2015, Waring and Currie 2009). The various forms of integration of managerial and professional governance tools may create new and hitherto unknown alliances between NPM and other political agendas like populism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…New modes of governing focused on physicians not only as objects but also as actors directly involved in governance (Kuhlmann et al 2013, McDonald et al 2008, Vicarelli and Pavolini 2017. As a result, boundaries between professionalism and managerialism and between professions and organisations are 'blurring' and new forms of more hybrid, integrated or transformative professionalism are emerging (Denis and van Gestel 2016, Kuhlmann and Burau 2015, Martin et al 2017, Noordegraaf 2015, Waring and Currie 2009). The various forms of integration of managerial and professional governance tools may create new and hitherto unknown alliances between NPM and other political agendas like populism.…”
Section: Methodsmentioning
confidence: 99%
“…, Vicarelli and Pavolini ). As a result, boundaries between professionalism and managerialism and between professions and organisations are ‘blurring’ and new forms of more hybrid, integrated or transformative professionalism are emerging (Denis and van Gestel , Kuhlmann and Burau , Martin et al . , Noordegraaf , Waring and Currie ).…”
Section: Governance Professionalism and Npm: Developing A Framework mentioning
confidence: 99%
“…In a health system that is still maturing, 1 2 policies aimed specifically at clinical leadership would provide a broad context and strategy to ensure that frameworks and guidelines exist to guide the roles and responsibilities of clinical leadership, and the training and development required to ensure effective clinical leadership. [39][40][41] Having policies on clinical leadership might help to address the enablers and hindrances identified at each of the levels.…”
Section: Balance Between Managerial and Leadership Rolesmentioning
confidence: 99%
“…Additionally, our survey reported that physicians believe that problem identification, leadership, healthcare delivery, policy recommendation and research should be the main roles of physicians in the healthcare system of Nigeria. These are some of the documented roles of physicians in healthcare system around the world [11,12]. Except healthcare delivery, the engagement of the Nigerian doctor in other identified roles is debatable and were specified has been grossly suboptimal.…”
Section: Discussionmentioning
confidence: 99%